2001
DOI: 10.1007/s15010-001-0025-1
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Encephalopathy with Seizure and Frontal Intermittent Rhythmic Delta Activity

Abstract: A 54-year-old woman was admitted to our clinic with frequent convulsions. Subsequently she developed a toxic look, rigidity, confusion and severe encephalopathy. Salmonella typhii was isolated from the blood cultures and she was diagnosed with Salmonella encephalopathy. The prominent electrophysiological finding was the frontal intermittent rhythmic delta activity (FIRDA) in electroencephalograph (EEG). After treatment EEG revealed normal activity. The presence of FIRDA is not a specific finding but this kind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Meningitis is an unusual complication of typhoid fever, with the majority of cases involving newborns and young infants and being associated with significant mortality (7,13,18). However, 5 to 35% of adult typhoid fever patients have signs and symptoms associated with the central nervous system such as seizure or acute psychotic behavior, confusion, and dizziness, usually occurring within the first few days of fever (28). In addition, a significant percentage of the patients who survive Salmonella meningitis suffer permanent neurological deficits (17).…”
Section: Discussionmentioning
confidence: 99%
“…Meningitis is an unusual complication of typhoid fever, with the majority of cases involving newborns and young infants and being associated with significant mortality (7,13,18). However, 5 to 35% of adult typhoid fever patients have signs and symptoms associated with the central nervous system such as seizure or acute psychotic behavior, confusion, and dizziness, usually occurring within the first few days of fever (28). In addition, a significant percentage of the patients who survive Salmonella meningitis suffer permanent neurological deficits (17).…”
Section: Discussionmentioning
confidence: 99%
“…Kauffman et al [2] reported a 71.4% mortality in their series of 14 adult patients with Salmonella meningitis. Mortality is highest for patients with a profound disturbance of consciousness [3]. Of those who did survive, a significant percentage was left with permanent neurological deficits, which appear to be more frequent with S. typhi.…”
Section: Discussionmentioning
confidence: 99%
“…Confusion, dizziness, seizure or acute psychotic behavior may occur in the 1st few days of fever, as late as the 3rd week or during convalescence [3].…”
Section: Discussionmentioning
confidence: 99%
“…S. typhi 5) IL-8 MCP-1 Fig. 4 Reported numbers of patients with enteric fever by year and affected regions.…”
Section: A Case Of Enteric Fever Complicated With Acute Encephalopathymentioning
confidence: 99%